Menutup Celah Eksploitasi dalam Transplantasi Organ Melalui Peran Akta Notaris - Salma Nabilah; R. Ismala Dewi; Pieter E. Latumeten (Badan Strategi Kebijakan Hukum, 2025)
The medical advancements in human organ transplantation hides a dark reality: illegal organ trafficking, donor identity fraud, and exploitation of the vulnerable individuals. Without strict oversight, these practices can lead to injustice and human rights violations. Notarial deeds serve as a legal safeguard, ensuring that every transplantation procedure is in accordance with regulations, remain transparent, and free from abuse. This article examines the strategic role of notarial deeds in guaranteeing the validity of the agreement between organ donors and recipients, as stipulated in Article 24 paragraph (1) letter d of the Minister of Health Regulation No. 38/2016. This research is doctrinal approach with a normative legal study based on relevant legal sources. The case study of Decision Number 464/Pid.Sus/2023/PN.Ckr and the findings at Dr. Saiful Anwar Hospital reveal various irregularities in the practice of human organ transplantation, including the involvement of intermediaries in illegal human organs transactions. A notarial deed is not just a formal document, but a legal instrument that protects the rights of the parties, ensures compliance with regulations, and closes loopholes for exploitation and abuse in human organ transplant procedures.